Paradoxes of thesis as qualification test - N. I. Martishina (Высшее образование в России, 2022)
The implicit contradiction between scientific and qualification aspects of thesis is considered in relation to the problem of scientific criteria. Logic of this problem and the broader problem of knowledge types demarcation determines the need to change thestandardized presentation of scientific results.